Utility of vaginal vault cytology in the local recurrence of cervical cancer - Kazuto Nakamura; Soichi Yamashita; Keiko Kigure; Toshio Nishimura; Ikuro Ito; Anri Azuma; Kohshiro Nakao; Ken Ando; Tatsuya Kanuma (BMC, 2023)
Abstract Background In Japan, 8000 women were newly diagnosed with cervical cancer in 2018. The healthcare insurance policy in Japan allows physicians to utilize vaginal volt cytology tests and serum biomarker measurement at every visit and imaging analysis at an adequate interval with screening for recurrence after initial treatment. However, the major surveillance guidelines published in the United States and European countries recommend focusing on pelvic examinations and symptom reviews to avoid unnecessary tests. This study aimed to reassess the benefits of standard surveillance methods adopted in this study by retrospective analysis. Methods From January 2009 to December 2015, the medical records of patients with recurrence who were initially diagnosed with International Federation of Gynecology and Obstetrics stage I-III cervical cancer were collected for this study. Clinicopathological data were statistically analyzed to identify significant factors. In the first 2 years, the patients underwent regular surveillance, including pelvic examination, serum tumor marker tests, vaginal vault cytology every 1-3 months, and imaging analysis at 6- to 12-month intervals. In the following 2 years, the patients received a regular check with the same methods every 4 months and an annual imaging analysis. Afterward, the patients had regular screening every 6 to 12 months. Results In the study period, 84 of the 981 patients experienced recurrence, and 88.1% had an asymptomatic recurrence. The disease-free interval was not related to the recurrence site. In univariate analysis, primary treatment, recurrence site, and diagnostic method were significant factors for survival outcomes. In contrast, multivariate analysis indicated that only primary treatment was a significant factor. In patients with local recurrence, multivariate analysis demonstrated that radiation as salvage therapy was an independent predictive factor for overall survival after recurrence. Conclusions In this retrospective study, routine imaging analysis and serum biomarker measurement did not contribute to patient prognosis after recurrence. In contrast, vaginal vault cytology can improve survival after recurrence in some patients. Tailored surveillance methods based on individual disease conditions and treatment modalities can improve post-recurrent survival outcomes.